KETERLIBATAN MASYARAKAT DALAM KEGIATAN KEPARIWISATAAN DI TAMAN NASIONAL BUNAKEN - Budiana Setiawan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2013)
Bunaken National Park is one of primadona tourism destinations of North Sulawesi Province. The development of tourism destination in Bunaken Nasional Park affects the exchanging of jobs of Bunaken society. Formerly, the jobs of Bunaken society were fishermen and farmers. Now, they exchange or at least addition their jobs in tourism activity, like boat rental, diving rental, diving guide, souvenir seller, handicraft maker, etc. Nevertheless, their business in tourism activity raises new conflicts that related with economic interests. The development of tourism destination in Bunaken National Park causes strengthening of old traditions and development of awareness of society for preserve marine parks from destructive activity.